Bank policies towards SME sector in Poland and selected countries worldwide - Joanna Duda; Maciej Wozniak (Managerial Economics)
Small- and medium-sized enterprises (SMEs) are very signifi cant for the economy. However, they face many problems when trying to fi nance their development. In connection to the above, the authors set four research questions that are connected with bank policies towards SMEs. Then, they make an analysis in order to answer the questions. The conclusions, recommendations. and limitations are presented at the end of the paper.